Research on Follow-up Purchase Behavior of Online Shopping Return - Yu Wang , Yanrui Jia , Weiying Chen (Forest Chemicals Review, 1970)
Online shopping has become an important way of shopping in people's life with the rapid development of network economy. At the same time, the return problem caused by a large number of transaction disputes is also restricting the development of online retail. Therefore, the research on the impact of online retailers' return policy on consumers has become a hot spot in recent years. Based on the literature review, this paper constructs the impact model of online retail return policy on consumers' back purchase behavior, and makes an in-depth study in the form of questionnaire, analyzes each return policy dimension on consumers' purchase intention, times, amount and quantity. Return policy dimensions include return amount, time limit, logistics cost bearing, simplicity of return process, merchants' handling attitude and limitations of return logistics mode selection. The study found that loose return policy can improve consumers' subsequent purchase behavior, but the influence degree of each dimension is different. Finally, this paper puts forward some suggestions on the formulation of return policy to online retailers.